Do static stress changes of a moderate‐magnitude earthquake significantly modify the regional seismic hazard? Hints from the L'Aquila 2009 normal‐faulting earthquake (Mw 6.3, central Italy). (16th August 2014) - Pace, Bruno; Bocchini, Gian Maria; Boncio, Paolo
Abstract We investigated the Coulomb stress changes in the active faults surrounding a moderate‐magnitude normal‐faulting earthquake (2009 L'Aquila, Mw 6.3) and the associated variations in the expected ground motion on regional probabilistic seismic hazard maps. We show that the static stress variations can locally increase the seismic hazard by modifying the expected mean recurrence time on neighbouring faults by up to ~290 years, with associated variations in the probability of occurrence of the maximum expected earthquake of up to ~2%. Our findings suggest that the increase in seismic hazard on neighbouring faults following moderate‐magnitude earthquakes is probably not sufficient to necessitate systematic upgrades of regional probabilistic seismic hazard maps, but must be considered to better address and schedule strategies for local‐scale mitigation of seismic risk.